Anaerobic Threshold is Significantly Enhanced by High Intensity Interval Training (HIIT) in Balinese Athletic Students - Indira Vidiari Juhanna (Journal of Global Pharma Technology, 2019)
Introduction: Anaerobic threshold is a physiological point when lactate production begins to exceed the lactate spent via oxidation process resulting in increasing amount of lactate in the circulation. It is an important aspect of sports physiology and several methods have been developed to enhance it. However, little study had conducted to evaluate the effectiveness of high intensity interval training (HIIT) in enhancing the anaerobic threshold. Method: A quasi experimental study with pre test and post test group design was conducted at Ngurah Rai Sports Building Square from January to February 2017. The subjects were randomly divided into two groups in which the first group received HIIT and the second one was the Steady State Training group performed for 2 minutes of sprint and 2 minutes of jogging for 6 weeks. Results: 24 male students were enrolled in this study with mean age 13.92±1.165 years for the first group (HIIT) and 14±1.128 years old in the second one (SST). The anaerobic threshold was significantly after the intervention (HIIT [before vs after]: 178.17±2.368 vs 197.83±3.460; SST: 177.17±1.586 vs 185.25±1.288; p: <0.05). The value difference (after-before) comparison between both groups also proved to be significantly different (HIIT vs SST: 19.67± 2.309 vs 8.08 ± 1.311; p<0.05). Conclusion: Both HIIT and SST were proved to significantly enhance the anaerobic threshold in male highschool students. However, HIIT had significantly higher enhancement compared to SST.Keywords: Anaerobic threshold, Steady State Training, lactate, high intensity interval training.